Influence of drying operating temperature difference on aroma (2AP) of Thai Pathumthani Fragrant Rice - Khomkaew, Sompot (Srinakharinwirot University Engineering Journal, 2021)
The study to quantify the loss of aroma substances 2-Acetyl-1-Pyrroline (2AP) of Thai Pathumthani Fragrant Rice in the dehumidification process was calculated from how much the aroma content 2-Acetyl-1-Pyrroline of dehumidified paddy was reduced from the aroma substance value 2-Acetyl-1-Pyrroline (2AP) in the aroma paddy. By recirculation batch drying process samples were collected every 2 hr in a 12 hr work cycle. 2-Acetyl-1-Pyrroline (2AP) =3.26 μg/g at temperature 390C due to the relatively lightly aroma content 2-Acetyl-1-Pyrroline (2AP), but when reducing the moisture content of the aroma paddy with a hot air dryer, the moisture content of the paddy at 18% is found. The aroma substance 2-Acetyl-1-Pyrroline (2AP) was between 2.08-3.72 μg/g and the aroma mean 2-Acetyl-1-Pyrroline (2AP) =2.69 μg/g at temperature 530C. 17.08± 12.43 μg/g Therefore, it can be seen that in the process of dehumidification, paddy causes a loss of aroma content 2-Acetyl-1-Pyrroline (2AP), which causes a decrease in the aroma of rice.